Recognition, Redistribution, and Liberty - Collins, Anne D.; Lim, Jamus Jerome (2012)
This paper examines the relationship between redistribution, recognition, and liberty. In particular, it critiques the existing approaches in the critical literature that either reduces redistribution to a simple subset of recognition, or insists that recognition is both necessary and sufficient for redistribution to occur. It argues, instead, that the introduction of the relatively weak assumption of (minimal) individual liberty is required for recognition, and that while recognition is necessary, it is insufficient for redistribution. It also considers the sustainability of voluntary redistribution in a liberal society, and voluntary recognition in an authoritarian society. Finally, the approach is applied to the problems of discrimination, genocide, and ethnic conflict.